Reinvigorating International Climate Policy: A Comprehensive Framework for Effective Nonstate Action. Issue 4 (9th November 2015) - Chan, Sander; van Asselt, Harro; Hale, Thomas; Abbott, Kenneth W.; Beisheim, Marianne; Hoffmann, Matthew; Guy, Brendan; Höhne, Niklas; Hsu, Angel; Pattberg, Philipp; Pauw, Pieter; Ramstein, Céline; et al.
Abstract: As countries negotiate a new climate agreement for the United Nations climate conference in December 2015, a groundswell of climate actions is emerging as cities, regions, businesses and civil society groups act on mitigation and adaptation, independently, with each other and with national governments and international organizations. The Paris conference provides a historic opportunity to establish a framework to catalyse, support, and steer these initiatives. Without such a framework, 'bottom‐up' climate governance runs the risk of failing to deliver meaningful results. Social science research highlights the need for a comprehensive approach that promotes ambition, experimentation and accountability, and avoids unnecessary overlaps. This article specifies functions and design principles for a new, comprehensive framework for sub‐ and nonstate climate actions that could provide effective coordination. Abstract : Through technical consultations with national governments, the framework will drive national climate aspirations, and will demonstrate proven approaches that allow for more ambitious national mitigation and adaptation commitments, particularly in subsequent rounds of nationally determined contributions and national adaptation plans and strategies.